Sosialisasi dan Pemasangan Lubang Resapan Biopori untuk Keberlanjutan Lingkungan - Ni Wayan Lasmi; Komang Widhya Sedana Putra P; Kadek Wulandari Laksmi P (Yayasan Inspirasi El Burhani, 2025)
Introduction: Inadequate water consumption and sewage disposal are prevalent in the urban environment, leading to flooding and pollution. Biopore infiltration pits are an excellent solution, but low public awareness and acceptance. Objective: The project aims at educating the population of South Denpasar on the benefits of biopore technology, providing practical training for its installation, and encouraging self-installation towards environmental sustainability. Method: The program was carried out on a single day, consisting of four phases: (1) education and socialization, (2) in-site training for biopore installation, (3) independent biopore installation by participants, and (4) monitoring and evaluation. Both theoretical descriptions and practical demonstrations were used to make participation easier for the community. Outcome: The program was successful in raising awareness and knowledge at the community level. Initially, the participants were not familiar with biopore technology. Towards the end of the exercise, they showed increased awareness and a desire to install biopores. Reduction in surface water collection and improvement in organic waste disposal was observed. Conclusion: The program succeeded in spreading environmental awareness and biopore adoption. Education and involvement are needed for sustainability over time.